f(x) = 3√(x - h) + kGiven any cube root function, say f(x) = 3√(x - 2) + 5, compare it with the general formula to get the values of h and k. On comparing f(x) = 3√(x - 2) + 5 with the general formula, you get
- h = 2
- k = 5
Now remember that in the above general formula, h is the horizontal translation and k is the vertical translation. So, first we will graph the parent function of all cube root functions, p(x) = 3√x.
The graph of the parent function p(x) = 3√x is as follows:
|Parent cube root function|
Now in order to graph the function f(x) = 3√(x - 2) + 5, so you have to translate the graph of p(x) = 3√x two units right and five units up. Doing that, the graph of f(x) = 3√(x - 2) + 5 is obtained,